2020
DOI: 10.1177/0960327120905961
|View full text |Cite
|
Sign up to set email alerts
|

Methylnitrosourea, dimethylbenzanthracene and benzoapyrene differentially affect redox pathways, apoptosis and immunity in zebrafish

Abstract: Cancer continues to be a major cause of mortality globally. Zebrafish present suitable models for studying the mechanisms of genotoxic carcinogens. The aim of this study was to investigate the interaction between oxidant–antioxidant status, apoptosis and immunity in zebrafish that were exposed to three different genotoxic carcinogens methylnitrosourea, dimethylbenzanthracene, benzoapyrene and methylnitrosourea + dimethylbenzanthracene starting from early embryogenesis for 30 days. Lipid peroxidation, nitric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…In vivo as well as in vitro studies reported that HAH or PAH exposure of fish or fish immune cells results in altered expression of pro-inflammatory cytokines like IL-1β, TNFα, IL-6, IL-8, or IFNγ [150,155,[169][170][171][172][173]. Additionally, global transcriptomic studies corroborate that exposure to AhR ligands modulates immune gene expression of fish [170,[174][175][176].…”
Section: Immune Transcriptional Responses Of Fish To Ahr-binding Xenobioticsmentioning
confidence: 77%
“…In vivo as well as in vitro studies reported that HAH or PAH exposure of fish or fish immune cells results in altered expression of pro-inflammatory cytokines like IL-1β, TNFα, IL-6, IL-8, or IFNγ [150,155,[169][170][171][172][173]. Additionally, global transcriptomic studies corroborate that exposure to AhR ligands modulates immune gene expression of fish [170,[174][175][176].…”
Section: Immune Transcriptional Responses Of Fish To Ahr-binding Xenobioticsmentioning
confidence: 77%